If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22q + -8 = -28 + 3q Reorder the terms: -8 + 22q = -28 + 3q Solving -8 + 22q = -28 + 3q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-3q' to each side of the equation. -8 + 22q + -3q = -28 + 3q + -3q Combine like terms: 22q + -3q = 19q -8 + 19q = -28 + 3q + -3q Combine like terms: 3q + -3q = 0 -8 + 19q = -28 + 0 -8 + 19q = -28 Add '8' to each side of the equation. -8 + 8 + 19q = -28 + 8 Combine like terms: -8 + 8 = 0 0 + 19q = -28 + 8 19q = -28 + 8 Combine like terms: -28 + 8 = -20 19q = -20 Divide each side by '19'. q = -1.052631579 Simplifying q = -1.052631579
| 35+-5=m | | -1+7=m | | -1+7m=35+-5m | | 5x+65=8x | | 7m+-1=35+-5m | | log(y^4)=12x+8 | | 7m-1=35-5m | | 16x+2y=230 | | (35436+764744)= | | -2x^2+2x-5=x^2 | | -2x^2-2x+5=x^2 | | 7x-15=-2x^2 | | 7x-15=2x^2 | | t^2+2t=-1 | | 2x^4-x^2-10x-8=0 | | 2t-cos(t)=0 | | (3+5i)(4+4i)=0 | | (2+4i)(3+3i)=0 | | 5-7a^2=-80 | | 15=3m-8 | | x(x-3)(x-3)=0 | | x^2-2mx+m^2-8m=0 | | 6i(4-12i)=0 | | 6p^4-12p^3+6p^2=0 | | p^4-2p^3+p^2=0 | | 4a+6b-2a= | | 10y^2-29y+21=0 | | 7a+3b-6a= | | (x+y-1)dx+(2x+2y+1)dy=0 | | 2a+3b-6a= | | -6=1-5n-1 | | 4x(7x-11)= |